The internet factor in the context of prevention and treatment of covid-19. To the problem statement - N. G. Neznanov; A. P. Kotsyubinsky; D. A. Kotsyubinsky (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2023)
The article notes that the Western model of civilization based on the cult of individual legal freedom, including a clear and optimistic picture of the future developing according to the laws of liberal progress based on this cult, has been significantly shaken in recent years due to the post-informational stage of development of society, and especially with the advent of the Internet. These factors contributed to the strengthening of distressing influences in society, leading to anxious expectations of the population as a reaction to the redundancy of the uncontrolled flow of information and, as a consequence, to the growth in the 21st century of the massive demand for global security. During the SARS-CoV-2 pandemic, biopolitical projects of total security have entered into the sphere of practical politics, with Western society failing to consider the issue of public security vs. human rights in an analytically impartial and critically free capacity as scientists, including specialists in the field of public health, did 10-15 years ago. The situation that has arisen reinforces the negative socio-psychological tendencies noted above. This circumstance makes it necessary to consider the situation of a pandemic from the point of view of the special role of its network information support and the nature of organizational and methodological measures aimed at combating disease.The article examines the socially destructive and socio-psychopathological aspects of the network era, fraught with the threat of the development of mass psychosis, which was most clearly manifested in the situation of a pandemic, regardless of the specific ideological attitudes of a particular social group. The network factor and organizational and methodological measures aimed at combating the coronavirus are analyzed in detail. It is concluded that it is necessary to correct the non-optimal trends that were revealed at the height of the network era both in public sentiment and in the actions of the authorities, in terms of a more effective fight against the SARS-CoV-2 pandemic. To this end, it is proposed to take into account the laws of the network era and be actively present in the Internet space, creating from within an informational counterbalance to the observed negative trends. Specific directions in the implementation of this work are listed.